Remote Working and Sustainability: A Bibliometric Mapping Analysis - Abdulrahim, Hiyam (Journal of Ecohumanism, 2024)
This bibliometric analysis explores 214 peer-reviewed studies on Remote working and Sustainability that are accessible in the Web of Science database between 1997 and 2023. The study methodically investigates important aspects, such as primary publications, scientific information sources, authors, citations, co-occurrences, geographical origin, nation distribution, and authors' research output, using the R programming language for mapping. Apart from showcasing the existing status of research, the analysis seeks to identify gaps in the literature, forecast future directions, and identify recent hotspots and trends in the subject. The analysis highlights a notable absence of publications from Arab and less developed nations. Consequently, the study promotes greater understanding among academics in these areas, stressing the need to carry out excellent theoretical and empirical research on sustainability and remote working. Additionally, the study suggests promoting international scientific cooperation to incorporate these nations into the academic debate and increase the overall depth and breadth of findings on the subject.